Upaya Penggunaan Media Maket dalam Meningkatkan Minat Belajar Anak Kelompok B - Neni Budiani; Suzana Suzana (Program Studi Pendidikan Islam Anak Usia Dini Fakultas Tarbiyah UI BBC, 2021)
Playing while learning and learning while playing are the principles of learning in PAUD to stimulate children's interests and talents, however, this has not been implemented optimally, the impact of learning becomes monotonous, not attracting children's interest in learning. The purpose of this study was to increase children's interest in learning through the use of cardboard mockups and used materials specially designed in accordance with the characteristics of children aged 5-6 years. This Classroom Action Research was conducted in three cycles using the Kemmis Taggart model. Data were collected using observation techniques, performance tests and documentation. Data analysis through data reduction, data display, verification and conclusions. Quantitative data were analyzed with percentage analysis which was interpreted into qualitative data. The results showed that before the application of using make-in media the children's learning interest was low; The use of mock-ups in classroom play activities is carried out with teacher guidance, improved learning planning from the results of reflection, mock-up media innovation, and sub-theme differences. Mina learns that children get better after playing and learning with mock-up media. It was concluded that play and learning activities using mock-up media were effective in increasing interest in early childhood learning. The recommendation is the use of used goods in mock-up media activities to increase the ability of early childhood interest in learning. ABSTRAK Bermain sambil belajar dan belajar seraya bermain merupakan prinsip pembelajaran di PAUD untuk menstimulasi minat dan bakat anak, namun demikian hal tersebut masih belum dilaksanakan secara optimal, dampaknya pembelajaran menjadi monoton, tidak menarik minat belajar anak. Tujuan penelitian ini untuk meningkatkan minat belajar anak melalui penggunaan media maket dari kardus dan barang bekas yan dirancan khusus sesuai dengan karakerisiik anak usia 5 – 6 tahun. Penelitian Tindakan Kelas ini dilaksanakan selama tiga siklus dengan model Kemmis Taggart. Data dikumpulkan dengan teknik observasi, tes unjuk kerja dan dokumentasi. Analisis data melalui reduksi data, display data, verifikasi dan kesimpulan. Data yang bersifat kuantitatif dianalisis dengan analisis persentase yang diinterpretasikan menjadi data kualitatif. Hasil penelitian menunjukkan bahwa sebelum penerapan bermamenggunakan media make in kegiatan minat belajar anak anak rendah; Penggunaan maket dalam kegiatan bermain di kelas dilakukan dengan bimbingan guru, perbaikan perencanaan pembelajaran dari hasil refleksi, inovasi media maket, dan perbedaan sub tema. Mina belajar anak semakin baik setelah bermain dan belajar dengan media maket. Disimpulkan bahwa kegiatan bermain dan belajar dengan media maket efektif untuk meningkatkan minat belajar anak usia dini. Rekomendasinya adalah pemanfaatan barang bekas pada kegiatan membuat media maket guna peningkatan kemampuan minat belajar anak usia dini.